Prognostic value of the new IASLC/ATS/ERS classification of clinical stage IA lung adenocarcinoma. Issue 2 (November 2015) - Murakami, Shuji; Ito, Hiroyuki; Tsubokawa, Norifumi; Mimae, Takahiro; Sasada, Shinsuke; Yoshiya, Tomoharu; Miyata, Yoshihiro; Yokose, Tomoyuki; Okada, Morihito; Nakayama, Haruhiko
Highlights: The new adenocarcinoma classification has prognostic value in clinical stage IA. Lymphatic or vascular invasion were frequent in solid or micropapillary-subtype. Recurrence was frequent in solid or micropapillary-subtype. The discrepancy between c- and p-stage was frequent at solid and micropapillary. Abstract: Objectives: We analyzed and validated the prognostic utility of the new International Association for the Study of Lung Cancer (IASLC)/American Thoracic Society (ATS)/European Respiratory Society (ERS) for clinical stage IA lung adenocarcinoma (ADC) classification of adenocarcinoma (ADC). Methods: We retrospectively reviewed 347 patients with clinical stage IA nonmucinous ADC, who had undergone complete resection. The histological subtype was classified according to the predominant subtype, as proposed by the new IASLC/ATS/ERS ADC classification. Results: The histopathological subtypes, defined according to the new IASLC/ATS/ERS ADC classification, were ADC in situ (AIS) in 56 patients (16.1%), minimally invasive ADC (MIA) in 15 (4.3%), lepidic-predominant ADC in 109 (31.4%), papillary-predominant ADC in 70 (20.2%), acinar-predominant ADC in 61 (17.6%), solid-predominant ADC in 30 (8.6%), and micropapillary-predominant ADC in 6 (1.7%). The 5-year disease-free survival (DFS) rate was 100% for both AIS and MIA. All cases of recurrence involved invasive ADC. The 5-year DFS for lepidic-predominant ADC was 99.0%; acinar-predominant ADC, 82.4%; papillary-predominant ADC, 80.8%; solid-predominant ADC, 73.6%; and micropapillary-predominant ADC, 33.3%. The predominant subtype of ADC was significantly correlated with DFS ( P  < 0.0001). Multivariate analysis indicated that the pathological stage was an independent predictor of DFS ( P =  0.031). Other independent predictors of increased risk of recurrence were the presence of vascular or lymphatic invasion (HR = 4.96, P  = 0.001), and a pathological stage more advanced than IB (HR = 2.87, P  = 0.010). The coincidence between the clinical stage and pathological stage was 79.8%. The stage migration was found in 53.3% of solid-predominat ADC and in 83.3% of micropapillary-predominant ADC. Conclusion: The new IASLC/ATS/ERS ADC classification has prognostic value in predicting the recurrence and survival of patients with clinical stage IA ADC. The frequency of stage migration was found in more than half of solid and micropapillary predominant ADCs.